2014
DOI: 10.1017/s0950268814002027
|View full text |Cite
|
Sign up to set email alerts
|

Stool submission data to help inform population-level incidence rates of enteric disease in a Canadian community

Abstract: Laboratory-based surveillance data is essential for monitoring trends in the incidence of enteric disease. Current Canadian human enteric surveillance systems report only confirmed cases of human enteric disease and are often unable to capture the number of negative test results. Data from 9116 hospital stool specimens from the Waterloo Region in Canada, with a mixed urban and rural population of about 500 000 were analysed to investigate the use of stool submission data and its role in reporting bias when det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Annual Salmonella positivity rates were similar or slightly higher for males than for females, with the highest rates observed in the younger age groups, <5, 5-9 and 10-14 years. The observed seasonality and annual trends of positivity rates for both pathogens are congruent with reports from other countries [14,18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Annual Salmonella positivity rates were similar or slightly higher for males than for females, with the highest rates observed in the younger age groups, <5, 5-9 and 10-14 years. The observed seasonality and annual trends of positivity rates for both pathogens are congruent with reports from other countries [14,18].…”
Section: Discussionsupporting
confidence: 89%
“…It was found that adults and the elderly suffered increasingly more frequently from campylobacteriosis; this could be related to the frequent use of proton pump inhibitors and comorbidities in these age groups [2,26,27]. Others have also observed increasing test numbers among the elderly and related it to changes (increases) in healthcare-seeking and physicians' testing behaviour [14,18,24]. Additionally, the Swiss population aged ≥85 years increased by 29% from 2003 to 2012, which probably also contributed to the observed increase in test numbers [28].…”
Section: Positivity Rates In Relation To Age and Sexmentioning
confidence: 99%
“…The estimated relative contribution of each food type is dependent upon the probability that the food is involved in outbreaks that are identified and successfully investigated. For example, cases of severe illness or illness in children tend to be more frequently notified and cases of young adults less frequently [45]; this may also be true for outbreaks. Thus, certain risk groups within the larger population and smaller outbreaks may be underrepresented in the available data and more data are required to improve these estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Public health surveillance for different pathogens causing AG is dependent upon cases consulting for their illness, physicians requesting appropriate tests, identification of pathogens in laboratories and reporting of laboratory-confirmed cases to the public health authorities. Therefore physicians who request stool or other specimens for microbiological testing are essential contributors to the surveillance [1, 2]. A better understanding of the factors that influence General Practitioner (GP) diagnostic practices is needed to more accurately interpret laboratory-based surveillance data and the extent to which it underestimates the actual burden of disease.…”
Section: Introductionmentioning
confidence: 99%